Silver Nanoparticles Fabrication, Characterization and Applications - Maaz, Khan (IntechOpen, 2018)
Silver nanoparticles are the subject of immense interest because of their distinct chemical and physical properties that are different from their bulk counterpart. This makes these nanoparticles very important in many fields including antimicrobial applications, biosensor materials, composite fibers, cryogenic superconducting materials, cosmetic products, and electronic components. This book aims to provide in-depth study and analysis of various fabrication, characterization, and application techniques of silver nanoparticles that lead these nanoparticles very important in the recent technology. This book presents deep understanding of the new techniques from basic to the advanced level. This book addresses scientists, engineers, doctoral and postdoctoral fellows, and technical professionals working in specialized fields.